Contributions of single-cell genomics to our understanding of planktonic marine archaea. (7th October 2019) - Santoro, A. E.; Kellom, M.; Laperriere, S. M.
Abstract : Single-cell genomics has transformed many fields of biology, marine microbiology included. Here, we consider the impact of single-cell genomics on a specific group of marine microbes—the planktonic marine archaea. Despite single-cell enabled discoveries of novel metabolic function in the marine thaumarchaea, population-level investigations are hindered by an overall lower than expected recovery of thaumarchaea in single-cell studies. Metagenome-assembled genomes have so far been a more useful method for accessing genome-resolved insights into the Marine Group II euryarchaea. Future progress in the application of single-cell genomics to archaeal biology in the ocean would benefit from more targeted sorting approaches, and a more systematic investigation of potential biases against archaea in single-cell workflows including cell lysis, genome amplification and genome screening. This article is part of a discussion meeting issue 'Single cell ecology'.